INFLUENCE OF EMOTIONAL INTELLIGENCE AND TEACHING METHOD TOWARDS LISTENING SKILL - Ary Iswanto (LPPM Universitas Bina Sarana Informatika, 2015)
The aim of the research is to know the effect of teaching method and emotional intelligence towards student’s listening skill. The writer applied the purpose sampling to determine the sample. The technique of collecting data of teaching method and emotional intelligence used Likert scales or questioners and the Listening Skill test was acquired from the test multiple choice of 20 items. The research methodology that is used explanatory experimental and technique of data analysis that used in this research is regression analysis model. It was used to know the effect of independent variable to dependent variable. The statistic test used t-test and data analysis used correlation technique and partial regression. The research findings are:1). There is effect of Teaching Method towards Student’s Listening Skill. The result of the research is obtained by sig value = 0.000 < 0.05. It means that there is significance different of Student’s Listening Skill of the students who are taught by audio lingual teaching method and Student’s Listening Skill who are taught by conventional method. 2). There is effect of Emotional intelligence towards Student’s Listening Skill. The result of the test is obtained by sig value = 0.000 < 0.05. It means that there is significance difference of Student’s Listening Skill of the students whose High Emotional intelligence with Student’s Listening Skill of the students whose Low Emotional intelligence. 3). There is interaction between Teaching Method and Emotional intelligence towards Student’s Listening Skill at Private Junior High School in South Jakarta. The result of the test is obtained by sig value = 0.043 < 0.05.